New' and 'old' social risks: Life cycle and social class perspectives on social exclusion in Ireland - Christopher T. Whelan; Bertrand Maître (The Economic and Social Research Institute (ESRI), 2008)
The life cycle concept has come to have considerable prominence in Irish social policy debate. However, this has occurred without any systematic effort to link its usage to the broader literature relating to a concept. Nor has there been any detailed consideration of how we should set about operationalising the concept. In this paper we make use of Irish EU-SILC 2005 data in developing a life cycle schema and considering its relationship to a range of indicators of social exclusion. At the European level renewed interest in the life cycle concept is associated with the increasing emphasis on the distinction between 'new' and 'old' social risks and the notion that the former are more 'individualised'. An important variant of the individualisation argument considers globalisation to be associated with increased but much more widely diffused levels of risk. Inequality and poverty rather than being differentially distributed between social classes are thought to vary between phases in the average work life. This position contrasts sharply with the emphasis on cumulative disadvantage over the life course. Our findings suggest that both the 'death of social class' and cumulative disadvantage over the life cycle theses are greatly over blown. A more accurate appreciation of the importance of new and old social risks and the manner in which they are both shaped by and influenced by welfare state strategies requires that we systematically investigate the manner in which factors such as the social class and the life cycle interact. Our evidence suggests that such an approach rather than leading us to jettison our concern with social class is likely, as Atkinson (2007) argues, to leave us more impressed by the degree to which the 'slayers' of class are themselves 'riddled with class processes'.
Keywords: 330; Soziale Ungleichheit; Randgruppe; Soziale Schicht; Lebenszyklus; Irland